Model Pendidikan Moderasi Beragama Berbasis Transformative Learning di MAN 1 Yogyakarta: Strategi Adaptif dalam Konteks Era Post-truth - Salsabila Nur Imatul Adzillah; Achadi, Muh. Wasith (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2024)
This study aims to examine the implementation model of religious moderation at MAN 1 Yogyakarta in responding to the challenges of the post-truth era, marked by widespread disinformation and shifts in religious values. Using a qualitative case study approach, the research focuses on strategic design, institutional support, and the impact of the program on students’ character development. The values of moderation are integrated into the curriculum, extracurricular activities, and school culture to shape students who are critical, tolerant, and inclusive. The findings indicate that MAN 1 Yogyakarta has successfully internalized moderation through innovative programs such as SANDI MAS, the Islamic History Tour, and interfaith dialogue. These programs have had a positive impact on improving students’ cognitive understanding, affective attitudes, and social behavior. The model reflects a transformative learning approach that strengthens critical religious literacy and pluralistic values in addressing contemporary ideological challenges. This study recommends that other Islamic educational institutions adopt an integrative approach that combines pedagogical, cultural, and personal dimensions to foster a moderate, tolerant, and diversity-oriented generation.